Kajian Hukum Pidana Penyalahgunaan Dana BOS: Pertanggungjawaban Pidana, Efektivitas Regulasi, dan Rekomendasi Kebijakan: Criminal Law Review of BOS Fund Misuse: Criminal Liability, Regulatory Effectiveness, and Policy Recommendations - Diah Ayu Pitaloka; Yogi Prasetyo; Ardhana Januar Mahardhani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The School Operational Assistance Fund (BOS) is a government program that aims to improve the quality and accessibility of education through school operational funding. However, in practice, various irregularities in the management of BOS Funds continue to be found, with the potential to cause state financial losses and to violate the principles of accountability and transparency. The problem in this study is the forms of misuse of BOS Funds and the imposition of criminal liability on perpetrators under the provisions of criminal law in Indonesia. This study aims to analyze the forms of misuse of BOS Funds, examine the criminal liability of perpetrators, and examine the application of the Corruption Eradication Law and the technical regulations governing the management of BOS Funds. The research method used is normative juridical, with a statutory approach, a case approach based on court decisions, and a review of relevant legal literature. The results of the study indicate that misuse of BOS Funds is generally carried out through mark-up practices, fictitious reports, noncompliant procurement, and deductions from funds by certain individuals. These actions satisfy the elements of criminal corruption, including abuse of authority, unlawful acts, and acts that enrich oneself or others at the expense of the state, resulting in state financial losses. The conclusion of this study emphasizes the need to strengthen the monitoring system, increase budget transparency, and implement strict criminal sanctions to prevent the recurrence of BOS Fund misuse.